2012
DOI: 10.5038/1936-4660.5.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Numeracy, Financial Literacy, and Financial Decision-Making

Abstract: Financial decisions, be they related to asset building or debt management, require the capacity to do calculations, including some complex ones. But how numerate are individuals, in particular when it comes to calculations related to financial decisions? Studies and surveys implemented in both the United States and in other countries that are described in this paper show the level of numeracy among the population to be very low. Moreover, lack of numeracy is not only widespread but is particularly severe among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 36 publications
8
81
1
8
Order By: Relevance
“…The general pattern of inadequacies documented in this journal by Lusardi (2012) and Gilliland et al (2011) with respect to debt and money management among consumers is apparently paralleled by comparable deficiencies for entrepreneurs. In our case study, 50% of business owners (7/14 businesses) did not regularly review financial statements, and 86% (6/7) of those businesses were experiencing financial difficulties; conversely, 50% (7/14) of the businesses in the study were experiencing financial difficulties, and for 86% (6/7) of them, the business owner did not regularly review the financial statements.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The general pattern of inadequacies documented in this journal by Lusardi (2012) and Gilliland et al (2011) with respect to debt and money management among consumers is apparently paralleled by comparable deficiencies for entrepreneurs. In our case study, 50% of business owners (7/14 businesses) did not regularly review financial statements, and 86% (6/7) of those businesses were experiencing financial difficulties; conversely, 50% (7/14) of the businesses in the study were experiencing financial difficulties, and for 86% (6/7) of them, the business owner did not regularly review the financial statements.…”
Section: Resultsmentioning
confidence: 73%
“…The second cause of failure, according to Ropega, is insufficient capital, including excessive debt and poor capital management (33.5% and 33 %, respectively, of respondents in the Polish study). These figures are reminiscent of those reported by Lusardi (2012) with respect to deficiencies in the understanding of personal credit: fewer than 36% of research respondents correctly answered questions related to credit cards and interest rates, and over 20% indicated they did not know the answer.…”
Section: Small Businessmentioning
confidence: 59%
See 1 more Smart Citation
“…The rest of the survey focuses on four key components of financial capability-making ends meet, planning ahead, managing financial products, and financial knowledge and decision-making The survey also includes a self-assessment of mathematical ability. The full NFCS questionnaire is available at www.USFinancialCapability.org, and a comprehensive overview of the NFCS data is provided in Lusardi (2011).…”
Section: Datamentioning
confidence: 99%
“…To begin, researchers have found that mathematical ability is connected not only to wage increases and likelihood of fulltime employment (Rivera-Batiz 1992; Eide and Grogger 1995;Levy et al 1995), but also forward thinking in one's personal finances (Lusardi 2012;Nye and Hillyard 2013). In addition, numeracy is linked with better decision-making (Peters et al 2006;Jasper et al 2013), nutrition label understanding (Rothman et al 2006), as well as with better risk comprehension in healthcare (Fagerlin et al 2007;Lipkus and Peters 2009).…”
Section: Motivation For Numeracymentioning
confidence: 99%